Assessment of legal framework of the digital copyright infringements of audio-visual services in the European Union - Gromkova, Polina (Riga Graduate School of Law, 2021)
Today, perhaps the most global problem on the Internet is the problem of Internet piracy, which is closely related to the accompanying problem - copyright infringement. Everything is “leaked” to the Internet: from music and pre-premieres of films to unpublished scientific papers and confidential documents. The reason for this phenomenon is, first of all, imperfect and ineffective legislation, both at the level of global and national level. Despite that, there are other factors such as economy and psychology that influence piracy. Statistics show that audiovisual content falls onto the category of most violated type of media, thus should be observed more critically. Technological progresses happen so fast, that it is very hard to create a homogenous system for copyright protection and think through the potential types of infringements that Internet may bring.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Copyright